2015
DOI: 10.1016/j.ahj.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cost comparison of transcatheter and operative closures of ostium secundum atrial septal defects

Abstract: Background Clinical outcomes for transcatheter and operative closures of atrial septal defects (ASDs) are similar. Economic cost for each method has not been well described. Methods A single-center retrospective cohort study of children and adults <30 years of age undergoing closure for single secundum ASD from January 1, 2007, to April 1, 2012, was performed to measure differences in inflation-adjusted cost of operative and transcatheter closures of ASD. A propensity score weight-adjusted multivariate regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…Previous studies have demonstrated that TC-ASD has lower cost and shorter LOS than O-ASD(5,36). Over the study period, there were no significant changes in either following TC-ASD.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have demonstrated that TC-ASD has lower cost and shorter LOS than O-ASD(5,36). Over the study period, there were no significant changes in either following TC-ASD.…”
Section: Discussionmentioning
confidence: 97%
“…The risk of procedure-associated death in isolated TC-ASD in published series are 0–0.15%(30,34,35). The best estimates of risk-adjusted procedural mortality following O-ASD, as derived from the Society for Thoracic Surgeons Congenital Heart Surgeons Database, are between 3–9 per 1,000(5,36,37). Though there is risk standardization in these large series, care should be exercised in comparing outcomes between studies and the absolute risk of mortality with each procedure remains low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations